KONSTRUKSI REALITAS DI MEDIA ONLINE (STUDI ANALISIS FRAMING TERHADAP PEMBERITAAN RUU PERMUSIKAN DI MEDIA ONLINE DETIK.COM) - Faizuddin Rahmatulloh; Yanuar Luqman (Interaksi Online, 2020)
Information has become one of the main needs of society today. As a platform that is easily accessed and presented with full information, online media such as Detikcom are the first choice for the community. We often find many differences in how the news reported by online media. This is caused by differences in point of view and media agendas powned by media itself. The difference in how the news reported is a result of the reality created by the media which has a direct effect on the community that shapes understanding of the issue/event. This research tries to define the form of framing conducted by Detickcom in reporting the issue of RUU Permusikan. This research used Pan and Kosicki framing analysis method to decode the news. The result of this research indicate that Detikcom has interest in siding to DPR RI as the compiler of RUU Permusikan by presenting them as the dominanty party. Detik construct Jajak pendapat RUU Permusikan as an initial form of cooperation between musician and DPR RI in drafting process of RUU Permusikan. Detikcom tried to hide the fact that in this discussion that musicians found a lot of bug on the draft. This is intended to form a positive public perception of RUU Permusikan. Detik alignment also built by represent RUU Permusikan as a musician needs by feature only the postive point of view. In addition, Detik try to change th epublic perception